Effect of Amelioran Material on Soil Chemical Properties of Incubated Peat Planting Media in Polybag - Syahminar Syahminar; Erwin Masrul Harahap; Abdul Rauf; Ali Jamil (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to obtain the best combination of types and doses of ameliorant materials: dolomite, rock phosphate, and mineral soil to improve the chemical properties of soil which was incubated for one year in peat media in polybag. The research was conducted in May 2015 - April 2016 in the experimental garden in the village of Sijambi, Tanjungbalai, North Sumatra. Elevation 3 m above sea level, with the C2 (Oldeman) climate type. The experiment was compiled using a Randomized Block Design, with 3 treatments of ameliorant material. The three ameliorant materials were tested for 3 doses. The addition of dolomite treatment: A1=0.45 kg polybag-1; A2=0.90 kg polybag-1; A3=1.35 kg polybag-1. The addition of rock phosphate treatment: A4=0.45 kg polybag-1; A5=0.90 kg polybag-1; A6=1.35 kg of polybag-1. The addition of mineral soil treatment: A7=0.45 kg polybag-1; A8=0.90 kg polybag-1; and A9=1.35 kg polybag-1.The results shown that the highest dose of dolomite (1.35 kg polybag-1) improved soil chemical properties, including soil pH and alkali cations (K, Ca and Mg) on incubated peat soil. Addition of rock phosphate with the highest dose of 1.35 kg polybag-1 (A6) increases available phosphorus and soil CEC. Addition of mineral soil dose of 0.90 kg polybag-1 (A8) increases soil CEC. In the analysis of total soil nitrogen, the highest increase was obtained by adding dolomite dose of 0.45 kg.polibag-1 (A1).